Metachronous liver metastases after long-term follow-up of endoscopic resection for rectal neuroendocrine neoplasms: a report of three cases - Yuma Hane; Takahiro Tsuchikawa; Kimitaka Tanaka; Yoshitsugu Nakanishi; Toshimichi Asano; Takehiro Noji; Yo Kurashima; Yuma Ebihara; Soichi Murakami; Toru Nakamura; Keisuke Okamura; Satoshi Takeuchi; et al. (Surgical Case Reports)
Abstract Background Rectal neuroendocrine neoplasms (NENs) are rare, but their incidence has increased in recent years. The metastasis rate is low in cases of a tumor diameter < 1 cm or depth of invasion lower than the submucosa; therefore, the European Neuroendocrine Tumor Society (ENETS) and the North American Neuroendocrine Tumor Society (NANETS) consensus guidelines recommend endoscopic resection. Since little has been reported on the long-term prognosis of endoscopic resection for rectal NEN, consensus is lacking regarding the follow-up period after endoscopic resection. Case presentation Here, we report three cases of metachronous liver metastasis after long-term follow-up of endoscopic mucosal resection (EMR) for rectal NEN. The pathological findings indicated a depth lower than the submucosa and complete radical resection in all cases and lymphovascular invasion in only one case. All three cases showed metachronous multiple liver metastases after 9–13 years of follow-up for EMR, despite achieving complete resection and without muscular invasion. Conclusions Metachronous liver metastases may occur after long interval following endoscopic resection; thus, long-term follow-up is necessary after endoscopic resection for rectal NEN.